Pengembangan E-Modul Kimia Berbasis Proyek pada Materi Larutan Elektrolit dan Non Elektrolit - Indah Sari Sihombing; Marham Sitorus (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to (1) to determine the results of the analysis of chemistry teaching materials on electrolyte and non-electrolyte solution materials used in schools according to BSNP standards, (2) to develop e-modules for electrolyte and non-electrolyte solution materials according to the BSNP eligibility criteria and have been based on projects, and (3) To determine student learning outcomes after being given project-based e-modules. The population in this study were all students of class X MIA SMA Negeri 1 Deli Tua, totaling 6 classes. The sample in this study was class X MIA 5 who was taught with a project-based chemistry e-module. The instrument used is an e-module feasibility questionnaire according to the BSNP standard, a learning outcome test of 20 questions that have been tested valid. This study uses the method and media development (R&D) with the ADDIE model. The ADDIE model has several stages, namely Analysis, Design, Develop, Implementation, and Evaluation. Where the results of the feasibility analysis of the content feasibility aspect of the e-module are 3.82; language eligibility is 3.83; The feasibility of presenting 3.81 and the feasibility of graphics 3.77 means that the teaching materials from the trial are very valid based on the BSNP. The average student learning outcomes who are taught project-based e-modules in one class are 78.8095. The results of the right-hand t-test with t count = 4.147> t table = 2.086. Thus the criteria for testing the hypothesis t count > t table are met. This means that Ho is rejected, Ha is accepted, so it can be concludedthat the project based chemistry learning e-module developed is better in improving students' chemistry learning outcomes in electrolyte and non-electrolyte solution materials.